Prevention of low back overuse injuries in alpine ski racing - What do we know and where do we go from here? - Spörri, J.; Haid, C.; Kröll, J.; Jahnel, R.; Fasel, B.; Müller, E. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The goal of this study is to present an overview of what is known about the epidemiology and causes of low back overuse injuries in general, and in Alpine ski racing in particular. Furthermore, it gains perspectives on potential prevention measures that specifically address the loading patterns of Alpine ski racing.